The treatment of myocardial ischemia-reperfusion injury: potential roles of natural drug modulating CaMKII - Yang, Kai; Zhang, Ping; Hui, Xianshan; Liu, Chao; Li, Jun; Liu, Yongmei (Frontiers in Pharmacology, 2026)
Myocardial ischemia-reperfusion injury (MIRI) represents a significant challenge in the treatment of cardiovascular diseases, with its complex pathogenesis involving multiple signaling pathways, such as calcium overload, oxidative stress, inflammatory responses, and cell apoptosis. Calcium/calm-odulin-dependent protein kinase II (CaMKII), a key calcium signaling transducer molecule, plays a central regulatory role in the onset and progression of MIRI. We conducted a comprehensive review of the literature on phytochemicals targeting CaMKII as a protective mechanism against MIRI. The search was performed across multiple databases, including PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), and Google Scholar, covering the period from January 2000 to September 2025. A total of 254 articles were retrieved, of which 16 were included in this review. Molecular docking was then performed to evaluate the binding affinity between natural drugs and CaMKII. This paper systematically summarizes the latest research findings on natural drugs that alleviate MIRI by targeting the CaMKII signaling pathway, with a particular focus on the mechanisms of action of representative natural drugs and their experimental validation in animal and cellular models. The aim is to provide a theoretical basis and research directions for the development and clinical application of natural drugs, thereby promoting innovation in prevention and treatment strategies for myocardial ischemia-reperfusion injury.